PENGEMBANGAN MODUL PEMBELAJARAN BERBASIS CONTEXTUAL TEACHING AND LEARNING (CTL) PADA MATERI STATISTIKA KELAS VII MTsN KURANJI PADANG - Lestari, Debi Ayu (Pendidikan Matematika, 2014)
Teaching material that used by students during math learning do not give opportunity to students in contruction self concept. Besides, it doesnât guide students to find the way to give material in the text book in math learning less variation. In hadling the problem , it can be done with developing teaching material such as module base on contextual teaching and learning validly and practically for statistic material at VII grade students. The research used developing research , it is done by using IDI (Intructional Develop Institute). It define step, it is done by analizing sylabus and teaching material that used by the teacher. Module had been validated by one indonesia lecture and ane math teacher. That, it is done practice theartment at islamic junior hight school kuranji padang VII grade students. It is done to see practicality in using module. The result showed that module in math learning base on contextual teaching and learning have been devolped was valid. Base on questioner have been given to student in seeing practicallity was including to practice category. It meens that, module which is used have been practice, interest, and bonefit for teacher and student in learning process. It concludes that module base on contextual teaching and learning in math learning is valid and practice.